THE EFFECT OF USING DIGITAL WALLETS AND FINANCIAL LITERACY ON CONSUMPTIVE BEHAVIOR OF STUDENTS IN DKI JAKARTA - Nuratika, Oktavia; Mukhtar, Saparuddin; Wiralaga, Harya Kuncara (Faculty of Economics and Business, Universitas Negeri Jakarta, 2022)
This study aims to determine the influence of use digital wallet and financial literacy on the consumptive behavior of students in DKI Jakarta. The research method used was a survey method with a quantitative approach. The population in this study was students with a campus location in DKI Jakarta. The study sample 192 respondents who were determined by the lemeshow formula because the number of the population was unknow. Data collection techniques using questionnaires. The data analysis technique used is multiple linear regression analysis. The results showed that the use of digital wallet and financial literacy had a partial and simultaneous effect on consumptive behavior. The use of digital wallet has a positive and significant effect on consumptive behavior, while financial literacy has a negative and significant effect on consumptive behavior.